Design of composite bridges with integral abutments. Issue 1 (January 2017) - Pak, Daniel; Bigelow, Hetty; Feldmann, Markus
Abstract: Dedicated to Prof. Dr. Akimitsu Kurita on his 70th birthday Bridges are of vital importance to Europe's infrastructure and composite bridges have already become a popular solution in many countries, representing a well‐established alternative to concrete bridges. Their competitiveness depends on several factors such as site conditions, local costs of materials and labour and the contractor's experience. One outstanding advantage of composite bridges compared with concrete bridges is that the steel girders can carry the weight of the formwork and the fresh concrete during casting. Another major advantage is savings in construction time, which reduces disturbance to traffic and, consequently, saves money for the contractor, but even more so for road users – a fact that has been neglected for a long time. Recently, this factor has increasingly attracted attention as the latest studies show the need to take into account not only simple production costs, but also construction time and maintenance costs when deciding on a specific bridge type. All these needs are met by integral abutment bridges as well. In addition, this bridge type has the potential to outclass traditional bridges with transition joints as it not only reduces production and maintenance costs, but saves on economic and socio‐economic costs as well.